2021
DOI: 10.1002/ase.2048
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory Feelings About Dissection: An Exercise for the First Day of a Gross Anatomy Course

Abstract: Studies have demonstrated that students experience a variety of intense emotions in anticipation of human anatomical dissection, including enthusiasm, gratitude, responsibility, apprehension, detachment, anxiety, and spiritual or moral reflection. The exercise described here provides an opportunity to start a conversation about the complexity of students' emotional reactions to the anatomy experience. The intention of this exercise is to normalize the variety of emotions that anatomy students experience, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 69 publications
(95 reference statements)
0
15
0
Order By: Relevance
“…Moreover, physical symptoms, such as nausea and appetite loss were found to accompany such activities frequently but to then diminish gradually (Vikani et al, 2016). The benefits of this learning experience may be maximized by using a guided discussion (Zumwalt, 2021), while physical and psychological difficulties following anatomy laboratory sessions can be decreased by orientation, group discussion with health care professionals, and positive interactions between the students and their teachers (Singroha et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, physical symptoms, such as nausea and appetite loss were found to accompany such activities frequently but to then diminish gradually (Vikani et al, 2016). The benefits of this learning experience may be maximized by using a guided discussion (Zumwalt, 2021), while physical and psychological difficulties following anatomy laboratory sessions can be decreased by orientation, group discussion with health care professionals, and positive interactions between the students and their teachers (Singroha et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, a study that assessed the emotional impact of cadaver dissection on physical therapy students indicated that the experience reduced post‐traumatic stress symptoms (Curfman et al, 2018). Moreover, research suggests that anatomy teachers can prepare, mentor, and assist students who participate in anatomy laboratory courses by encouraging pride and self‐confidence, promoting a positive emotional experience, and sustaining a sense of respect for human dignity (Chang et al, 2018; Zumwalt, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Its claim, built solely on perceptions of students and teaching faculty appears to be marked by consistent indications of student anxiety, discomfort, and lack of confidence in their ability to meet expectations of high‐quality outcomes. In fact, an increasing number of papers describe efforts designed to help students prepare for the stress of learning anatomy before embarking on an anatomy course (Houwink et al, 2004; Iaconisi et al, 2019; Zumwalt et al, 2021; Attardi et al, 2022a), coping with the pressure of performance anxiety during the anatomy course (Bernhardt et al, 2012; Bellier et al, 2020) and develop basic dissection skills using low fidelity activities in preparation for cadaveric‐based learning (Yakura et al, 2022). Very few studies suggest that dissection coupled with associated educational activities is an effective pedagogical strategy for learning (Pizzimenti et al, 2016).…”
Section: Is Dissection the Most Effective Tool In The Hands Of The No...mentioning
confidence: 99%
“…Overall, the authors agree with Patera and Khamuani's proposal (2021) to provide support and guidance during students' cadaveric gross anatomy laboratory, although it is not clear what intervention would be most appropriate. This personal encounter with death and dying can be emotionally challenging, but it provides an opportunity for students to learn how to handle and cope with stressful situations, which will be an important skill as they move into clinical experiences (Zumwalt, 2021). Rather than leaving students to process this unique and somewhat difficult situation on their own, it is important for them to have some type of guidance.…”
Section: )mentioning
confidence: 99%